PERAN GURU BIMBINGAN DAN KONSELING PADA SISWA YANG MENGALAMI KURANG MOTIVASI BELAJAR DARI KELUARGA BROKEN HOME DI SMP NEGERI 3 BANJARBARU - Apriyanty, Dian (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2018)
Broken home is usually used to describe a family that is not harmonious and does not walk like a harmonious and prosperous family due to frequent conflicts that cause disputes that can even lead to divorce. This will have a major impact on the household atmosphere that is no longer conducive, parents no longer pay attention to their children, thus triggering negative behavior in development, especially in the psychological child. This research of individual counseling counseling services for broken home students aims to determine the role of individual counseling services from students who are Broken Home, as well as to find out how students can obtain motivation in learning at school.This research is the type of interview. The interviews used in the study were false in structure. The purpose of this type of interview is to find the problem more openly, where the parties invited to the interview are asked for their opinions and ideas (Sugiyono, 2007). Data analysis techniques performed on the analysis activities in this study focused on the data collection process taking place in the form of: reduction, display data, conclusion / verification miles and huberman.The results of this study are students who are Broken Home in order to have a high sense of responsibility for themselves, besides that they should not do negative actions that can harm themselves and the future, and are advised to study diligently and diligently so as to increase their motivation for achievement. For Guidance and Counseling Teachers at the school concerned to give more serious attention and guidance to students from the Broken Home family as a motivation and motivation to learn in order to get better performance. Keywords: Broken Home, Counseling, and motivation